Exploring the interplay between Eimeria spp. infection and the host: understanding the dynamics of gut barrier function - Pan Chen; Mujeeb Ur Rehman; Yanfeng He; Aoyun Li; Fuchun Jian; Longxian Zhang; Shucheng Huang (Veterinary Quarterly)
Coccidiosis is a global disease caused by protozoans, typically including Eimeria spp., which pose a significant threat to the normal growth and development of young animals. Coccidiosis affects mainly the gut, where parasite proliferation occurs. The intestinal barrier, which consists of chemical, mechanical, biological, and immune defences, plays a crucial role in protecting the host against pathogens, xenobiotics, and toxins present in the gastrointestinal tract. When animals ingest sporulated Eimeria spp. oocysts, these parasites primarily reproduce in the intestinal tract, causing damage to the structure and function of the intestine. This disruption of intestinal homeostasis adversely affects animal health. Numerous studies have also revealed that Eimeria-infected animals experience slower bone growth rates, inferior meat quality, reduced egg production and quality, as well as impaired growth and development. Therefore, the purpose of this review is to examine the underlying mechanisms through which Eimeria spp. regulate intestinal damage and disturb the balance of the internal environment. Specifically, this review will focus on their effects on the structural basis of the host intestine’s chemical, mechanical, biological and immune barriers. This understanding is crucial for the development of effective drugs to prevent the invasion of Eimeria spp. into the intestine, which is of paramount importance for maintaining host health.